From policy to practice: uptake of pre-exposure prophylaxis among adolescent girls and young women in United States President's Emergency Plan for AIDS Relief-supported countries, 2017–2020. (15th June 2022) - Patel, Pragna; Sato, Kimi; Bhandari, Neeta; Kanagasabai, Udhayashankar; Schelar, Erin; Cooney, Caroline; Eakle, Robyn; Klucking, Sara; Toiv, Nora; Saul, Janet
Abstract : Background: The US President's Emergency Plan for AIDS Relief's (PEPFAR) first implemented pre-exposure prophylaxis (PrEP) for HIV prevention through the Determined, Resilient, Empowered, AIDS-Free, Mentored and Safe (DREAMS) partnership in 2016. PrEP is a critical intervention to achieve the main objective of DREAMS, reducing new HIV infections among 15-14 year old adolescent girls and young women (AGYW) in 15 high HIV burdened countries. Methods: We describe uptake of PrEP among AGYW in PEPFAR. Most PrEP programs screened persons who tested HIV-negative for eligibility and offered PrEP as part of combination prevention with follow-up, including repeat HIV testing and counseling, at 3-month intervals. Platforms providing comprehensive services for AGYW were also leveraged. We examined two PEPFAR monitoring indicators, using the FY20Q4 Monitoring, Evaluation, Reporting (MER) indicator dataset to assess progress in PrEP uptake, and descriptive narratives to understand successes and challenges from fiscal year 2017 to 2020. To assess coverage, we calculated the PrEP to Need ratio (PnR) using a published methodology. Results: From FY2017 to FY2020, 576570 total clients initiated PrEP and the number of PEPFAR countries offering PrEP doubled from 12 to 24. Of 360073 (62% of total) initiations among women, 52% were among AGYW with steady increases from year to year. Among all AGYW, 20–24–year-old women represented a significantly higher proportion of PrEP initiators than adolescents (15–19years) (64 versus 36%, P   <  0.05). Of all 186985 PrEP initiations among AGYW, 99% were in DREAMS countries. Barriers, such as low demand and adherence, were addressed through outreach efforts, including mobile sites, use of technology to educate and support AGYW, media campaigns, and engaging peers in program implementation. We saw a 2.5-fold increase in PrEP uptake among AGYW from 2018 to 2019; by 2020, all DREAMS countries were implementing PrEP. However, PrEP coverage among AGYW in DREAMS countries remains low (PnR range: 0–4.1); only two have a PnR greater than 1 where there were more PrEP users than new HIV diagnoses. Conclusion: PrEP uptake among AGYW has grown since 2016; however, challenges remain. Tools to improve adherence are needed to improve PrEP persistence among AGYW. National policies to facilitate greater PrEP uptake among adolescents would be beneficial. A greater need for PrEP in DREAMS countries is evident and if realized, will contribute to epidemic control.